Workshop on Domain Specific Approaches to Software Test Automation: In Conjunction With the 6th ESEC/FSE Joint Meeting 2007
DOI: 10.1145/1294921.1294926
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of approaches to feature testing in the mobile phone applications domain

Abstract: Software engineering is a discipline that cannot be applied based solely on elegant theories. Real software production requires software solutions that may apply a mixture of engineering and ad-hoc practices in a systematic way. In this sense, experimentation is staple for identifying the best practices and solutions for a given software development problem. This paper presents results from an experimental evaluation of the use of model-based testing and the use of exploratory testing in the context of feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Muccini et al [27] mention the need for specialized approaches to create tests for mobile applications, taking into account characteristics that directly influence the testing activity highlighting connectivity, limited resources, autonomy, user interface, context awareness, adaptation, new operating systems and languages programming, diversity of settings, and touch screen devices. As a result, the testing of mobile applications introduces new challenges that must be overcome and have been addressed in scientific and technical research in the areas of software engineering and mobility [ [13]. These works can be divided into two lines.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Muccini et al [27] mention the need for specialized approaches to create tests for mobile applications, taking into account characteristics that directly influence the testing activity highlighting connectivity, limited resources, autonomy, user interface, context awareness, adaptation, new operating systems and languages programming, diversity of settings, and touch screen devices. As a result, the testing of mobile applications introduces new challenges that must be overcome and have been addressed in scientific and technical research in the areas of software engineering and mobility [ [13]. These works can be divided into two lines.…”
Section: Related Workmentioning
confidence: 99%
“…In later studies, Nascimento and Machado [13] investigated the use of exploratory testing using Labeled Transition Systems.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the above, a number of publications using controlled experiments dealing with software testing in general exist (e.g., [1,5,15,16,20]). However, these do not cover independent software testing.…”
Section: Related Workmentioning
confidence: 99%
“…Proposals for ET use and improvement have also been made in empirical studies. Do Nascimento et al [13] proposed that ET is used to acquire knowledge for model based testing. More recently, Itkonen et al [8] showed how the application of the testers' knowledge during ET sessions can explain the high efficiency of ET.…”
Section: Related Workmentioning
confidence: 99%